Analysis of Tourist Interest Patterns Toward Tourism Destinations in NTB: A Descriptive Study Based on Google Trends Data 2024–2025 - Baiq Herdina Septika; Menik Aryani; Afrida Nur Chasanah (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study analyzes tourist interest patterns toward tourism destinations in West Nusa Tenggara (NTB) Province using Google Trends data for the period January 2024–December 2025. Employing a descriptive qualitative approach with secondary data, this research identifies fluctuations in search interest based on the Interest Over Time and Related Queries variables for major NTB destination keywords. The findings reveal that tourist interest follows predictable seasonal patterns, peaking during Eid holiday (April–May), the dry season (July–September), and year-end holidays (December). International events, particularly MotoGP Mandalika, generate significant spillover effects on overall NTB destination search interest. New destinations such as Kuta Mandalika demonstrate greater responsiveness to digital promotion stimuli compared to established destinations. Related Queries analysis further reveals that tourists seek comprehensive information covering accommodation, transportation, and activities, suggesting that digital content strategies must be developed holistically. These findings provide practical implications for NTB tourism marketing practitioners in designing timely and data-driven digital promotion strategies. Keywords: Tourist Interest; Tourism destination, digital marketing, Google Trends.